Retrospective analysis of antiretroviral therapy uptake and retention of male clients receiving methadone maintenance therapy in two provinces in Vietnam: potential synergy of the two therapies. Issue 1 (December 2017) - Pham, Linh; Kitamura, Akiko; Do, Hoa; Lai, Kim; Le, Nhan; Nguyen, Van; Kato, Masaya
Abstract Background Vietnam has a concentrated HIV epidemic with injection drug use being the dominant mode of HIV transmission. Vietnam has rapidly expanded antiretroviral therapy (ART) and methadone maintenance therapy (MMT). This study aims to analyze ART uptake and retention among male clients receiving MMT in Vietnam in the early phase of the MMT program. Methods The male clients (age ≥18) who were newly enrolled in care or started ART at two HIV clinics in Hanoi (2009 to 2011) and three HIV clinics in Can Tho (2010 to 2012) were included for the analysis. The CD4 lymphocyte count at HIV care enrollment and ART initiation and retention on ART were retrospectively analyzed. The values of those receiving MMT were compared with the values of two groups: those in whom injection drug use (IDU) status was documented, but were not receiving MMT, and all male clients not receiving MMT. To analyze retention, survival analysis with log rank test and Cox proportional hazard model was used. Results During the study period, 663 adult men were newly enrolled in HIV care (237 had IDU status documented) and 456 initiated ART (167 had IDU status documented). Among those who initiated ART, 28 were receiving MMT. At care enrolment, those receiving MMT had a median CD4 count of 230 (IQR 57–308) cells/mm3, while men self-reporting IDU and not receiving MMT and all men not receiving MMT had a median CD4 count of 158 (IQR 50–370) cells/mm3 and 143 (IQR 35–366) cells/mm3, respectively. At ART initiation, men receiving MMT had significantly higher CD4 count with median at 203 (IQR 64–290) cells/mm3 than men self-reporting IDU and not receiving MMT (80, IQR 40–220, cells/mm3, p = 0.038) and all men not receiving MMT (76, IQR 20–199, cells/mm3, p = 0.009). Those receiving MMT had a significantly higher retention rate than those self-reporting IDU but not receiving MMT (hazard ratio = 0.18, p = 0.019) and men not receiving MMT (hazard ratio = 0.20, p = 0.041). Conclusions Our analysis suggests that men receiving MMT in Vietnam are achieving relatively early uptake and high retention rates on ART. The findings support potential benefits of integrating MMT and ART services in Vietnam.